A detailed optical investigation of ZnO@ZnS core–shell nanoparticles and their photocatalytic activity at different pH values. Issue 5 (June 2015) - Sadollahkhani, Azar; Nur, Omer; Willander, Magnus; Kazeminezhad, Iraj; Khranovskyy, Volodymyr; Eriksson, M.O.; Yakimova, Rositsa; Holtz, Per-Olof
Abstract: In this study zinc oxide nanoparticles (NPs) were synthesized via a co-precipitation method and were covered by zinc sulfate using a chemical approach at a temperature of 60 °C forming ZnO@ZnS core–shell nanoparticles (CSNPs). In order to investigate the effect of the shell thickness on the optical and photocatalytic properties, many samples were grown with different concentration of the sulfur source. The results show that, covering ZnO with ZnS leads to form a type II band alignment system. In addition, the band gap of the ZnO@ZnS CSNPs was found less than both of the core and the shell materials. Also the emission peak intensity of the ZnO NPs changes as a result of manipulating oxygen vacancies via covering. The photocatalytic activity of the ZnO@ZnS CSNPs was investigated for degradation of the Congo red dye. As dye pollutants can be found in mediums with different pH, the experiments were performed at three pH values to determine the best photocatalyst for each pH. Congo red dye degradation experiments indicate that the ZnO@ZnS CSNPs act more efficiently as a photcatalyst at pH values of 4 and 7 compare to the pure ZnO NPs.